INTEGRATING STEM AND PJBL TO PROMOTE ENVIRONMENTAL AWARENESS IN PRESCHOOL (SDG 13) - Safitri, Dhian Gowinda Luh; Adhe, Kartika Rinakit; Widayanti, Melia Dwi; Malaikosa, Yes Matheos Lasarus; Simatupang, Nurhenti Dorlina (Universitas Muhammadiyah Surabaya, 2024)
This study investigated the effectiveness of an intervention aimed at enhancing early childhood education (PAUD) teachers' understanding and application of STEM (Science, Technology, Engineering, and Mathematics) and PJBL (Project-Based Learning). The intervention included professional development sessions, followed by pre-test and post-test assessments. Results indicated significant improvements in teachers' knowledge and pedagogical skills. The teachers' modules, created post-intervention, covered diverse themes such as disaster mitigation, resource management, and environmental conservation, reflecting their ability to integrate STEM and PJBL into engaging activities. The significant increase in post-test scores demonstrated the intervention's success in equipping teachers with the necessary skills to design and implement STEM-based learning using the PJBL approach. These findings suggest that such interventions are effective in enhancing early childhood educators' capabilities, ultimately benefiting young learners by providing them with enriching, real-life applicable educational experiences. This study highlights the importance of continuous professional development in advancing educational practices.